IMPLEMENTASI KOMUNIKASI PUBLIK DINAS DP3AP2KB KOTA SURAKARTA DALAM PENCEGAHAN KEKERASAN TERHADAP ANAK DI BAWAH UMUR - Tesa Pajar Nugraha; Sihabuddin Sihabuddin (Solidaritas, 2025)
The phenomenon of violence against children remains a serious issue in Surakarta, requiring appropriate implementation of public communication by the local government. This study aims to describe and analyze the implementation of public communication by the DP3AP2KB Surakarta City in preventing violence against minors. The theory applied refers to Hafied Cangara’s public communication model, which includes research, planning, implementation, evaluation, and reporting stages. This research employed a descriptive qualitative approach with data collected through in-depth interviews, observation, and documentation. Informants consisted of DP3AP2KB officials, Puspaga counselors, PPT coordinators, and community members as program recipients. The findings reveal that the implementation of public communication by DP3AP2KB is educational, persuasive, and participatory, carried out through socialization, counseling, the children’s forum, and family assistance services, using face-to-face methods, social media, and proactive outreach. This implementation has proven effective in increasing public understanding, awareness, and behavioral changes among parents in applying positive, non-violent parenting, although challenges remain, such as limited budget, human resources, and uneven public participation. Keywords: Implementation, Public Communication, DP3AP2KB, Child Violence Prevention